KINERJA PERUSAHAAN: APAKAH TATA KELOLA PERUSAHAAN DAN DIVERSITAS GENDER BERPENGARUH? - Ivone; Ivy Lee (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The main purpose of this study is to determine the effect of family ownership, institutional ownership, size of the board of directors, the presence of women, and the proportion of women on firm performance in family companies listed on the Indonesia Stock Exchange (IDX). By using secondary data obtained from the annual reports of sample companies in the period of 2016 – 2020. The sample companies selected using the purposive sampling method consist of 362 companies. This research uses panel data regression analysis with e-views application. The results of the study show that family ownership and sales growth have a positive influence on company performance. Firm size and firm age have a significant negative influence on firm performance. Meanwhile, other variables such as institutional ownership, size of the board of directors, the presence of women, the proportion of women, and control variables such as leverage and net profit margin have no significant effect on company performance.